Political Brands: Can Parties Be Distinguished by Their Online Brand Personality?. Issue 3 (3rd July 2018) - Rutter, Richard Nathan; Hanretty, Chris; Lettice, Fiona
Abstract : This paper investigates whether five English political parties are differentiating themselves based on the brand personality they are communicating through their websites. The relative brand positions of five English political parties are analyzed using Aaker's brand personality scale. The text from each party website is analyzed using content analysis and a dictionary-based tool. The results are plotted in relation to one another on a correspondence analysis map. We find that the two main dimensions on which parties' brand personalities differ relate to the trade-offs between communicating competence and communicating sincerity and between communicating sophistication and communicating ruggedness. We find that parties' brand personalities are distinctive, with the exception of the Green Party, and that the position of one party, the United Kingdom Independence Party, is particularly distinctive. Our research uses Aaker's existing framework for thinking about brand personalities, rather than creating a new framework for politics. By using an existing framework, we are able to use tools developed in other disciplines and show their usefulness for the study of political marketing.